PENGEMBANGAN STRATEGI PEMBELAJARAN GERAK DAN LAGU UNTUK OPTIMALISASI KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN DI TK TUNAS RIMBA 1 DAN TK INSAN CITA MADANI SAMARINDA - Budi Rahardjo; Pratiwi Hidayati (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This study aims to determine the learning strategies of motion and song in terms of planning for optimization of kinesthetic intelligence, strategies for learning motion and song in terms of design for optimization of kinesthetic intelligence, movement and song learning strategies viewed from the process of optimizing kinesthetic intelligence in TK Tunas Rimba 1 and TK Cita Madani Samarinda employees. This type of research is the development of the ADDIE Research And Development model. Development of motion and song learning models through 4 stages, namely: the stage of information gathering (analysis), b) Design, c) the stage of product development, d) the implementation and evaluation stages. Data collection techniques in this study used observation, interview, documentation and questionnaire techniques. The results showed that the process of optimizing kinesthetic intelligence through the development of motion learning strategies and songs was very well developed. This can be seen with the support of learning design consisting of syllabus, RPPM, RPPH, teaching materials, SOP and media. Based on the results of quantitative analysis calculations based on the One Sample Test table it is known that the significance value (2-tailed) is 0.082 <0.05. Then H0 is rejected and Ha is accepted, meaning that there is optimization of kinesthetic intelligence through motion and song learning strategies that are reviewed from planning, design, process at TK Tunas Rimba 1 and TK Insan Cita Madani Samarinda.